EVALUASI PENERAPAN PEMBELAJARAN DI TAMAN KANAK-KANAK: KURIKULUM BIDANG MOTORIK - Pamula Trisna Suri; Anton Komaini; Damrah Damrah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
The problem in this study is the rise of kindergartens that provide calistung learning because to enter the next level some elementary schools apply the calistung test. While in early childhood there should be several fields that must be developed, one of which is the physical motor field. This study aims to see the suitability of the kindergarten curriculum, especially in the motor field in the learning process. This type of research is an evaluation of the evaluative approach, CIPP research design (Context, Input, Process, Product). The informant researcher was a kindergarten teacher from Kemala Bayangkari 3 in Fifty District, Pekanbaru City. Data collection techniques by interview, observation and documentation methods. Research Results 1) context evaluation in the evaluation of the motor curriculum in Kemal Bayangkari 3 Kindergarten learning is in accordance with curriculum 13, 2) evaluation of input in the evaluation of the motor curriculum, namely the suitability of the qualifications of kindergarten teachers, namely diplomas or bachelors of Early Childhood Education and Infrastructure Facilities used by Kemal Bayangkari 3 Kindergarten in accordance with the Infrastructure Facilities Standards, namely good, 3) evaluation of the process of implementing the motor curriculum of Kemal Bayangkari 3 Kindergarten is included in the good category, 4) evaluation of products resulting from the learning process of the motor curriculum, namely students develop according to expectations in accordance with STPPA